2017
DOI: 10.1111/myc.12638
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and antifungal susceptibility of Fusarium isolates in onychomycosis

Abstract: Fusarium species have emerged as an important human pathogen in skin disease, onychomycosis, keratitis and invasive disease. Onychomycosis caused by Fusarium spp. The infection has been increasingly described in the immunocompetent and immunosuppressed hosts. Considering onychomycosis is a difficult to treat infection, and little is known about the genetic variability and susceptibility pattern of Fusarium spp., further studies are necessary to understand the pathogenesis and better to define the appropriate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 35 publications
6
29
3
1
Order By: Relevance
“…This finding is not compatible with the previous epidemiological evaluations conducted in Iran and other countries worldwide in which dermatophyte family and Candida species were, respectively, introduced as the most common agents of onychomycosis . However, our finding is similar to others where Aspergillus and Fusarium species were the predominant agents of fungal nail infection . Aspergillus species are growingly reported as the principal agents of non‐dermatophyte onychomycosis worldwide with a prevalence of as high as 59.8% in Malaysia, 42.7% in Tunisia, 50% in Brazil, 69.3% in Iran and up to 83% in Korea .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding is not compatible with the previous epidemiological evaluations conducted in Iran and other countries worldwide in which dermatophyte family and Candida species were, respectively, introduced as the most common agents of onychomycosis . However, our finding is similar to others where Aspergillus and Fusarium species were the predominant agents of fungal nail infection . Aspergillus species are growingly reported as the principal agents of non‐dermatophyte onychomycosis worldwide with a prevalence of as high as 59.8% in Malaysia, 42.7% in Tunisia, 50% in Brazil, 69.3% in Iran and up to 83% in Korea .…”
Section: Discussioncontrasting
confidence: 99%
“…Similar results were observed in a study performed by Guevara‐Suarez et al in Colombia, who identified the members of F. solani species complex, including F. falciforme , F. keratoplasticum , F. lichenicola and F. petroliphilum , as well as species of Fusarium oxysporum species complex. In the current study, for the first time, F. proliferatum was identified as the predominant species; however, F. keratoplasticum was the second common isolate similar to the results obtained by Rosa et al . Of all antifungal agents, only the new imidazoles, namely luliconazole and lanoconazole, as well as new triazoles, including efinaconazole, posaconazole and voriconazole, respectively, showed remarkable and moderate activities against Fusarium isolates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They are known to be opportunistic microorganisms which may cause local or systemic infections and present the most diverse antifungal resistance panel of drugs that include voriconazole, posaconazole, and amphotericin B. Clinical manifestation depends on the immune status of the host being neutropenia the major risk factor for acquiring infections . Fusariosis represents the second most prevalent cause of systemic filamentous fungal infection after aspergillosis .…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, invasive Fusarium infections are identified in 40–60% of blood cultures being the fungus identified in 60–80% of the patients presenting cutaneous lesions ,,. The mortality of disseminated Fusarium infections to immunocompromised patients ranges from 50 to 70% being related to the therapy ,,,,…”
Section: Introductionmentioning
confidence: 99%